The Theoretical Description for the Electrochemical Determination of Sucralose and Aspartame in Drinks - Volodymyr Tkach; Tetiana V. Morozova; Nataliia P. Shapovalova (Orbital: The Electronic Journal of Chemistry)
In this work, the electrochemical determination of sucralose and aspartame in drinks has been theoretically evaluated. Considering the accepting character of both sucralose chlorine atom and aspartame molecule, cathodic process is preferred. The theoretical description for VO(OH)-assisted electroanalytical process has proven the efficiency of the cathodic electroanalytical process for both of the sweeteners, despite of the augmented probability of the oscillatory behavior.